Mesoporous ceramic ball for cigarette and preparation method thereof

By using mesoporous ceramic balls, the problem of traditional fragrance-carrying materials being prone to water absorption and mold during storage and transportation is solved, and the fragrance adsorption ability and the safety of tobacco products are improved through the characteristics of high specific surface area and anti-extrusion strength.

CN119817848APending Publication Date: 2025-04-15FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510217236.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional tobacco fragrance-carrying materials are prone to absorb water and cause mold during storage and transportation, and have insufficient ability to absorb fragrances and harmful substances, which cannot meet the needs of modern tobacco products for high quality and health and safety.

Method used

Mesoporous ceramic balls for smoke made of mesoporous silica SBA-15, vapor-phase silica, water-washed kaolin, calcined kaolin, magnesium, alumina fibers, perlite and other materials are used to form particles with high specific surface area and anti-extrusion strength through high temperature calcination and special molding processes.

Benefits of technology

This mesoporous ceramic ball can effectively adsorb fragrance and aqueous solution, improve fragrance loading and stability; at the same time, by adsorbing nicotine and tar, the release of harmful substances is reduced and the safety and quality of tobacco products are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119817848A_ABST
    Figure CN119817848A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of tobaccos, in particular to a mesoporous ceramic ball for cigarettes and a preparation method of the mesoporous ceramic ball. The mesoporous ceramic ball disclosed by the invention is rich in pore structure and super-large in specific surface area, essence molecules can be firmly locked, conditions are provided for adsorption of essence and an aqueous solution, and the fragrance carrying amount can reach 30%-50% of the weight of the mesoporous ceramic ball. While the essence is released, the mesoporous ceramic ball can effectively adsorb nicotine and tar generated by tobacco combustion by virtue of a special physical and chemical structure, and the intake of harmful substances is synchronously reduced in the smoking process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tobacco, and in particular to a mesoporous ceramic ball for tobacco and a preparation method thereof. Background Art

[0002] With the development of society and the increasingly stringent requirements of consumers for the quality of tobacco products, the tobacco industry is facing the pressure of continuous upgrading and innovation. In the pursuit of the unique taste of cigarettes and the journey of reducing the harm of smoking to human health, the research and development of tobacco additive carriers has become a key link.

[0003] Traditional aroma materials are widely used in the tobacco field, among which adding natural plant powder and starch is quite common. Natural plant powder, with its natural aroma components, can give tobacco a certain flavor characteristic, and to a certain extent meet consumers' initial demand for aroma. Starch, with its good adhesion, helps additives to adhere and disperse during tobacco processing. However, the disadvantages of these traditional materials are becoming more and more prominent. On the one hand, natural plant powder and starch are extremely hydrophilic, and during the storage and transportation of tobacco, they are very easy to absorb moisture in the environment, which in turn causes mildew. This not only seriously damages the original flavor quality of tobacco, causing the loss of aroma and the growth of odor, but may also produce harmful substances such as mycotoxins, posing a potential threat to the health of smokers.

[0004] Traditional materials are limited by their relatively simple and poorly regular microstructures. In terms of the amount of flavor adsorbed by existing flavor carriers, due to their limited specific surface area, they cannot provide sufficient adsorption sites for flavor molecules to attach, making it difficult to achieve the ideal level of flavor loading and unable to meet the pursuit of strong and lasting aroma of tobacco products. Traditional flavor carriers are almost powerless in the adsorption of nicotine and tar. During the smoking process, harmful substances such as nicotine and tar are released in large quantities and inhaled by the human body, which continuously aggravates the damage caused by smoking to the respiratory system, cardiovascular system, etc. Mesoporous silica SBA-15 is synthesized by the organosilicon template method, resulting in its high cost, and the market price is in the range of 2500-5000 yuan / kg. The price of fumed silica with a large specific surface area is 80-190 yuan / kg. After using silica alone for granulation, there are problems of low crushing strength and low flavor adsorption. This is because the extrusion effect during the granulation process greatly reduces the pores and specific surface area of ​​the material.

[0005] In summary, in view of the defects of traditional aroma carrier materials in terms of safety, aroma carrier efficiency, adsorption of harmful substances and physical properties of particles, there is an urgent need for a high-efficiency aroma carrier and moisturizing material that can fully meet the needs of modern technology, so as to promote the development of tobacco products towards higher quality, healthier and safer directions. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a mesoporous ceramic ball for tobacco and a preparation method thereof, which solves the technical problem in the prior art that natural plant powder and starch aroma filler easily absorb moisture in the environment during tobacco storage and transportation, thereby causing mildew.

[0008] (II) Technical solution

[0009] In the first aspect of the present invention, the present invention provides a mesoporous ceramic ball for cigarettes, which is made of the following raw materials in the following proportions by weight: 8-20 parts of mesoporous silica SBA-15, 25-54 parts of fumed silica, 7-34 parts of washed kaolin, 7-34 parts of calcined kaolin, 5-35 parts of brucite, 0.3-5 parts of sodium carbonate, 1.4-7 parts of polyvinyl alcohol, and 120-160 parts of water.

[0010] Optionally, the polyvinyl alcohol and water are mixed to form a 1%-4% aqueous solution.

[0011] Optionally, the raw materials of the mesoporous ceramic balls for cigarettes further include 5-35 parts by mass of alumina fibers, 0.3-5 parts by mass of magnesium hydroxide, and 5-34 parts by mass of perlite.

[0012] Optionally, the mesoporous ceramic balls for cigarettes are made of raw materials in the following proportions, measured by weight: 10-17 parts of mesoporous silica SBA-15, 28-50 parts of fumed silica, 10-30 parts of washed kaolin, 10-30 parts of calcined kaolin, 10-30 parts of brucite, 10-30 parts of alumina fibers, 1-3.5 parts of magnesium hydroxide, 10-30 parts of perlite, 1-3.5 parts of sodium carbonate, and 130-150 parts of a 1%-4% aqueous solution of polyvinyl alcohol.

[0013] In a second aspect of the present invention, the present invention provides a method for preparing the mesoporous ceramic balls for cigarettes according to the first aspect, the preparation method comprising the steps of:

[0014] The raw materials of mesoporous silica SBA-15, fumed silica, washed kaolin, calcined kaolin, brucite, alumina fiber, perlite, sodium carbonate and magnesium hydroxide are mixed evenly, and then a 1%-4% aqueous solution of polyvinyl alcohol is added and stirred into a powdery material with a granular feel;

[0015] The powdery material is extruded into particles by a granulator, shot blasted by a shot blasting machine to improve the sphericity, and sieved for sorting;

[0016] The sorted particles are dried, then calcined at 500-1050°C for 2-6 hours and cooled naturally.

[0017] Optionally, the powdered material is first subjected to preliminary extrusion molding by a 3 mm rotary granulator, and then extruded into particles by a 1.5 mm rotary granulator, the extruded particles are put into a shot blasting machine and shot blasted for 2.5-4 minutes, the particles are taken out and sorted using 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, and the particles that do not meet the size are re-granulated, shot blasted and sorted.

[0018] Optionally, the drying temperature is 80-150° C., and then the mixture is placed in a muffle furnace and heated to 660° C. at a heating rate of 10° C. / min, and calcined for 4 hours.

[0019] Optionally, particles with a particle size of 0.9 mm-1.2 mm and particles with a particle size of 1.2 mm-1.5 mm are selected through sorting.

[0020] Optionally, the method for preparing the mesoporous ceramic balls for tobacco further comprises the step of: adsorbing the mesoporous ceramic balls for tobacco and liquid flavors through an immersion adsorption method to carry the flavors.

[0021] More optionally, the particles and liquid essence are loaded into a rotating bottle in a mass ratio of 1:0.5, and the rotating bottle is placed on a rotating machine and rolled so that the liquid essence is naturally adsorbed into the particles.

[0022] In the third aspect of the present invention, the present invention provides a cigarette, which is added with the mesoporous ceramic balls for cigarettes described in the first aspect of the present invention, or the mesoporous ceramic balls for cigarettes prepared by the preparation method described in the second aspect of the present invention.

[0023] (III) Beneficial effects

[0024] Traditional materials are limited by their own structural characteristics and have limited adsorption capacity, resulting in poor stability of fragrance. The rich pore structure and ultra-large specific surface area of ​​the mesoporous ceramic balls of the present invention can firmly lock the fragrance molecules, providing conditions for the adsorption of fragrance and aqueous solution, and the fragrance carrying capacity can reach 30%-50% of its own weight.

[0025] Inorganic materials are selected as the basic components and are subjected to high-temperature calcination treatment, which completely eliminates the hidden danger of harmful components remaining. Natural plant powders in traditional aroma materials are prone to carry impurities such as microorganisms and insect eggs, and starch substances are very easy to absorb moisture and mold and deteriorate in a humid environment, which not only affects the quality of tobacco, but also may produce harmful substances such as mycotoxins, endangering the health of consumers. The present invention allows consumers to enjoy the aroma of tobacco without worrying about potential health hazards, which meets the strict requirements of the modern tobacco industry for product safety.

[0026] Nicotine and tar are the main harmful substances in tobacco smoke, and long-term inhalation can cause serious damage to the human respiratory system, cardiovascular system, etc. While releasing the flavor, the mesoporous ceramic balls of the present invention can effectively adsorb the nicotine and tar produced by tobacco combustion due to their special physical and chemical structure, and simultaneously reduce the intake of these harmful substances during the smoking process.

[0027] Broken aroma particles will not only cause material loss and affect production efficiency, but may also cause premature leakage of flavors, affecting the tobacco flavoring effect. The particles have an anti-extrusion strength of up to 5-15N, so that they can always maintain their intact shape and are not easy to break under the mechanical external forces of tobacco processing, such as high-speed mixing, extrusion molding, packaging and transportation.

[0028] The present invention innovatively adds inorganic materials such as kaolin, brucite, and perlite on the basis of silicon dioxide, successfully achieving effective cost reduction. Among them, the price of kaolin is 3-5 yuan / kg, brucite is 2-3 yuan / kg, perlite is 1-3 yuan / kg, and alumina fiber is 5-15 yuan / kg. The addition of kaolin significantly improves the crushing strength after granulation, and brucite plays a key role in supporting the network structure, effectively solving the problem of pore blockage caused by extrusion of mesoporous materials, thereby greatly increasing the specific surface area of ​​the material. Through this material composite method, not only the material performance is improved, but also good results are achieved in cost control. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Thermogravimetric analysis of Example 1 of the present invention;

[0030] Figure 2 This is the laser particle size analyzer analysis of Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0032] The mesoporous ceramic balls for cigarettes of the present invention are made of raw materials in the following proportions, measured by weight: 8-20 parts of mesoporous silica SBA-15, 25-54 parts of fumed silica, 7-34 parts of washed kaolin, 7-34 parts of calcined kaolin, 5-35 parts of brucite, 0.3-5 parts of sodium carbonate, 1.4-7 parts of polyvinyl alcohol, and 120-160 parts of water.

[0033] Furthermore, the mesoporous ceramic balls for cigarettes are made of raw materials in the following proportions, measured by weight: 10-17 parts of mesoporous silica SBA-15, 28-50 parts of fumed silica, 10-30 parts of washed kaolin, 10-30 parts of calcined kaolin, 10-30 parts of brucite, 10-30 parts of alumina fibers, 1-3.5 parts of magnesium hydroxide, 10-30 parts of perlite, 1-3.5 parts of sodium carbonate, and 130-150 parts of a 1%-4% aqueous solution of polyvinyl alcohol.

[0034] Among them, mesoporous silica SBA-15 has a regular and rich mesoporous structure, with uniform mesopore size and orderly arrangement, providing a large number of adsorption sites for flavor molecules. Its large specific surface area allows flavors and aqueous solutions to be efficiently attached to it, just like building countless "micro storage rooms" for the aroma, greatly improving the material's ability to carry fragrance.

[0035] Fumed silica has a high specific surface area and has a synergistic effect with mesoporous silica SBA-15, further expanding the space inside the material that can absorb fragrance and enriching the mesoporous structure. Its nano-scale particle form can be filled between other ingredients to ensure that fragrance can be stably absorbed under different conditions, ensuring the durability and stability of the fragrance-carrying effect.

[0036] Kaolin itself has good chemical and thermal stability, and can resist the damage to the material structure caused by external environmental factors (such as temperature and humidity changes). It supports the entire material structure like a "skeleton" to prevent the structure from collapsing due to physical external forces during processing, transportation or storage, so it can ensure that the particles maintain their intact shape.

[0037] The brucite and alumina fibers work together to significantly improve the compression strength of the particles. They are interwoven and distributed inside the material, forming a reinforced network structure similar to "reinforced concrete". When the particles are squeezed externally, the fibers can effectively disperse the stress and prevent cracks from forming and expanding, making the particles have an anti-compression capacity of up to 5N-15N, ensuring that they will not break in all links of tobacco production and maintaining stable product quality.

[0038] Sodium carbonate and magnesium hydroxide can adjust the pH of the system and increase the hardness of the particles.

[0039] Polyvinyl alcohol aqueous solution plays a key role in bonding granulation. It can bond the dispersed solid powder raw materials together. In the early stage of particle forming, it acts like "glue" to make the various components tightly bonded, laying the foundation for subsequent processing; under mechanical operations such as stirring and extrusion, particles with a certain shape and strength are gradually formed.

[0040] Example 1

[0041] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 15 kg of mesoporous silica SBA-15, 35 kg of fumed silica, 10 kg of washed kaolin, 10 kg of calcined kaolin, 10 kg of brucite, 10 kg of alumina fiber, 5 kg of perlite, 2 kg of sodium carbonate, 3 kg of magnesium hydroxide, and 140 kg of a 3% aqueous solution of polyvinyl alcohol.

[0042] After mixing the above raw materials evenly with a trough mixer, add 140 kg of 3% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into shape by a 3 mm rotary granulator, and then extruded into particles by a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 3 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0043] The particles were dried in an oven at 100° C., taken out and placed in a muffle furnace, and calcined at 660° C. at a heating rate of 10° C. / min for 4 hours. The particles were taken out after natural cooling.

[0044] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0045] The average hardness of 0.9mm-1.2mm particles was tested to be 6.8N, and the average hardness of 1.2mm-1.5mm particles was 8.6N; the mass of the adsorbed liquid essence was 30-33%.

[0046] Example 2

[0047] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 158 kg of mesoporous silica SBA-1, 25 kg of fumed silica, 7 kg of washed kaolin, 7 kg of calcined kaolin, 5 kg of brucite, 0.3 kg of sodium carbonate, 1.4 kg of polyvinyl alcohol, and 120 kg of water.

[0048] After mixing the above raw materials evenly with a trough mixer, add 121.4 kg of 1% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into a 3 mm rotary granulator, and then extruded into particles with a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 2.5 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0049] The particles were dried in an oven at 80° C., taken out and placed in a muffle furnace for calcination at a heating rate of 10° C. / min to 500° C. for 6 hours, and the particles were taken out after natural cooling.

[0050] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0051] The average hardness of 0.9mm-1.2mm particles was tested to be 2.8N, and the average hardness of 1.2mm-1.5mm particles was 4.6N; the mass of the adsorbed liquid essence was 30-33%.

[0052] Example 3

[0053] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 520 kg of mesoporous silica SBA-1, 54 kg of fumed silica, 34 kg of washed kaolin, 34 kg of calcined kaolin, 35 kg of brucite, 5 kg of sodium carbonate, 7 kg of polyvinyl alcohol, and 160 kg of water.

[0054] After mixing the above raw materials evenly with a trough mixer, add 167 kg of 4% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into a 3 mm rotary granulator, and then extruded into particles with a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 4 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0055] The particles were dried in an oven at 150° C., taken out and placed in a muffle furnace for calcination at a heating rate of 10° C. / min to 800° C. for 4 hours, and the particles were taken out after natural cooling.

[0056] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0057] The average hardness of 0.9mm-1.2mm particles was tested to be 16.8N, and the average hardness of 1.2mm-1.5mm particles was 18.6N; the mass of the adsorbed liquid essence was 30-33%.

[0058] Example 4

[0059] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 10 kg of mesoporous silica SBA-15, 28 kg of fumed silica, 10 kg of kaolin, 10 kg of brucite, 5 kg of alumina fiber, 0.3 kg of magnesium hydroxide, 20 kg of perlite, 1 kg of sodium carbonate, and 130 kg of a 3% aqueous solution of polyvinyl alcohol.

[0060] After mixing the above raw materials evenly with a trough mixer, add 130 kg of 3% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into shape by a 3 mm rotary granulator, and then extruded into particles by a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 3 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0061] The particles were dried in an oven at 130° C., taken out and placed in a muffle furnace for calcination at a heating rate of 10° C. / min to 900° C. for 5 hours, and the particles were taken out after natural cooling.

[0062] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0063] The average hardness of 0.9mm-1.2mm particles was tested to be 20.8N, and the average hardness of 1.2mm-1.5mm particles was 22.6N; the mass of the absorbed liquid essence was 30-33%.

[0064] Example 5

[0065] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 1517 kg of mesoporous silica SBA-1, 50 kg of fumed silica, 30 kg of kaolin, 30 kg of brucite, 35 kg of alumina fiber, 5 kg of magnesium hydroxide, 34 kg of perlite, 3.5 kg of sodium carbonate, and 150 kg of a 3% aqueous solution of polyvinyl alcohol.

[0066] After mixing the above raw materials evenly with a trough mixer, add 150 kg of 3% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into shape by a 3 mm rotary granulator, and then extruded into particles by a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 3.5 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0067] The particles were dried in an oven at 140° C., taken out and placed in a muffle furnace for calcination at a heating rate of 10° C. / min to 1000° C. for 2 hours, and the particles were taken out after natural cooling.

[0068] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0069] The average hardness of 0.9mm-1.2mm particles was tested to be 23.8N, and the average hardness of 1.2mm-1.5mm particles was 25.6N; the mass of the absorbed liquid flavor was 30-33%.

[0070] Example 6

[0071] The mesoporous ceramic balls for cigarettes in this embodiment are made of the following raw materials by weight: 13 kg of mesoporous silica SBA-15, 35 kg of fumed silica, 22 kg of washed kaolin, 22 kg of calcined kaolin, 18 kg of brucite, 3 kg of sodium carbonate, and 145 kg of 3% aqueous solution of polyvinyl alcohol.

[0072] After mixing the above raw materials evenly with a trough mixer, add 145 kg of 3% polyethylene aqueous solution and stir into a powdery material with a granular feel. The stirred material is initially extruded into shape by a 3 mm rotary granulator, and then extruded into particles by a 1.5 mm rotary granulator. The extruded particles are put into a shot blasting machine and blasted for 3 minutes. Take out the particles and sort them with 0.9 mm, 1.25 mm and 1.5 mm sorting sieves, sort out the particles that do not meet the size, and re-granulate and shot blast.

[0073] The particles were dried in an oven at 100° C., taken out and placed in a muffle furnace, and calcined at 660° C. at a heating rate of 10° C. / min for 4 hours. The particles were taken out after natural cooling.

[0074] Weigh the particles and put them into a rotating bottle, add liquid essence into the rotating bottle at a mass ratio of 1:0.5 and then cover the sealing cover; put the rotating bottle on a rotating machine and roll it for 30 minutes to allow the liquid essence to be naturally adsorbed into the particles, and seal and store after the adsorption is completed.

[0075] The average hardness of 0.9mm-1.2mm particles was tested to be 6.8N, and the average hardness of 1.2mm-1.5mm particles was 8.6N; the mass of the adsorbed liquid essence was 30-33%.

[0076] Comparative Example 1

[0077] The mesoporous ceramic balls for cigarettes in this comparative example include the following raw materials by weight: 15 kg of mesoporous silica SBA-15, 2 kg of sodium carbonate, and 140 kg of a 3% aqueous solution of polyvinyl alcohol.

[0078] The preparation method is the same as that of Example 1

[0079] Comparative Example 2

[0080] The mesoporous ceramic balls for cigarettes in this comparative example include the following raw materials by weight: 40 kg of fumed silica, 2 kg of sodium carbonate, and 140 kg of a 3% aqueous solution of polyvinyl alcohol.

[0081] The preparation method is the same as that of Example 1

[0082] In Example 1 of the present invention, the ceramic particles were characterized by thermogravimetric analysis and laser particle size analyzer analysis. In the thermogravimetric analysis experiment, the ratio of ceramic particles to loaded water was 1:0.5, and the loading amount was controlled at about 10 mg. During the experiment, the initial temperature was set to 30°C, and then the temperature was raised to 800°C at a rate of 30°C / min. The purge gas was air, and the flow rate was set to 50 mL / min. The experimental results are shown in Figure 1. Figure 1 As shown in the figure, the maximum weight loss temperature of the sample is 112.1℃, the maximum weight loss rate is -22.5, and the weight loss is 33%. As the temperature gradually increases, the water in the particles is slowly released, which shows that the mesoporous material plays a good slow-release role in it.

[0083] In the laser particle size analyzer analysis experiment, the ceramic particles were tested by the instrument, and the results were as follows: Figure 2 As shown, the particle size was measured to be between 0.9 mm and 1.2 mm.

[0084] Nicotine was determined according to the national tobacco industry standard YC / T156 "Determination of Nicotine in Total Particles of Cigarettes". Carbon monoxide was determined according to the national tobacco industry standard YC / T30 "Determination of Carbon Monoxide in the Gas Phase of Cigarette Smoke". Total particle matter and tar in cigarette smoke were determined according to the national standard GB / T19609 "Determination of Total Particles and Tar by Cigarette Smoking Machine". The specific test results are shown in Table 1.

[0085] Table 1 Flue gas chemical indexes of the embodiments of the present invention and the comparative examples

[0086]

[0087]

[0088] In summary, the mesoporous ceramic balls for cigarettes of the present invention provide a large number of adsorption sites for flavor molecules; their large specific surface area enables flavors and aqueous solutions to be efficiently attached thereto. The mesoporous ceramic balls for cigarettes of the present invention have a significant adsorption effect on harmful components in cigarettes and have a good harm reduction effect.

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A mesoporous ceramic ball for cigarettes, characterized in that: According to weight parts, it is made from the following raw materials: 8-20 parts of mesoporous silica SBA-15, 25-54 parts of fumed silica, 7-34 parts of washed kaolin, 7-34 parts of calcined kaolin, 5-35 parts of brucite, 0.3-5 parts of sodium carbonate, 1.4-7 parts of polyvinyl alcohol, and 120-160 parts of water.

2. The mesoporous ceramic ball for cigarettes according to claim 1, characterized in that: The polyvinyl alcohol and water are mixed to form a 1%-4% aqueous solution.

3. The mesoporous ceramic ball for cigarettes according to claim 2, characterized in that: The raw materials of the mesoporous ceramic balls for cigarettes also include 5-35 parts by weight of alumina fibers, 0.3-5 parts by weight of magnesium hydroxide, and 5-34 parts by weight of perlite.

4. The mesoporous ceramic ball for cigarettes according to claim 3, characterized in that: According to weight parts, it is made from the following raw materials: 10-17 parts of mesoporous silica SBA-15, 28-50 parts of fumed silica, 10-30 parts of washed kaolin, 10-30 parts of calcined kaolin, 10-30 parts of brucite, 10-30 parts of alumina fiber, 1-3.5 parts of magnesium hydroxide, 10-30 parts of perlite, 1-3.5 parts of sodium carbonate, and 130-150 parts of 1%-4% aqueous solution of polyvinyl alcohol.

5. The method for preparing mesoporous ceramic balls for cigarettes according to any one of claims 1 to 4, characterized in that: The preparation method comprises the steps of: The raw materials of mesoporous silica SBA-15, fumed silica, washed kaolin, calcined kaolin, brucite, alumina fiber, magnesium hydroxide, perlite and sodium carbonate are mixed evenly, and then a 1%-4% aqueous solution of polyvinyl alcohol is added and stirred into a powdery material with a granular feel; The powdery material is extruded into particles by a granulator, shot blasted by a shot blasting machine to improve the sphericity, and sieved for sorting; The sorted particles are dried, then calcined at 500-1050°C for 2-6 hours and cooled naturally.

6. The method for preparing mesoporous ceramic balls for cigarettes according to claim 5, characterized in that: First, the powdered material is initially extruded into shape by a 3mm rotary granulator, and then extruded into particles by a 1.5mm rotary granulator. The extruded particles are put into a shot blasting machine and shot blasted for 2.5-4 minutes. The particles are taken out and sorted with 0.9mm, 1.25mm and 1.5mm sorting sieves. The particles that do not meet the size are re-granulated, shot blasted and sorted.

7. The method for preparing mesoporous ceramic balls for cigarettes according to claim 5, characterized in that: The drying temperature is 80-150° C., and then the mixture is placed in a muffle furnace and heated to 660° C. at a rate of 10° C. / min, and calcined for 4 hours.

8. The method for preparing mesoporous ceramic balls for cigarettes according to claim 6, characterized in that: After sorting, particles with a particle size of 0.9mm-1.2mm and particles with a particle size of 1.2mm-1.5mm are selected.

9. A mesoporous ceramic ball for carrying tobacco flavors, which is obtained by adsorbing flavors on the mesoporous ceramic ball for tobacco prepared by the preparation method according to any one of claims 5 to 8.

10. A cigarette, characterized in that: The invention comprises the mesoporous ceramic ball for cigarettes as described in any one of claims 1 to 4, or the mesoporous ceramic ball for cigarettes prepared by the preparation method as described in any one of claims 5 to 8.